The fate of indefinite and low‐grade dysplasia in ulcerative colitis and primary sclerosing cholangitis colitis before and after liver transplantation. Issue 8 (29th August 2013) - Eaton, J. E.; Smyrk, T. C.; Imam, M.; Pardi, D. S.; Loftus, E. V.; Owens, V. L.; Talwalkar, J. A.
Summary: Background: Patients with primary sclerosing cholangitis (PSC) and ulcerative colitis (UC) are at an increased risk of colorectal neoplasia, but it is unknown if liver transplantation (LT) alters neoplasia progression. Aim: To examine the natural history of indefinite dysplasia (IND) and low‐grade dysplasia (LGD) that develop in patients with PSC‐UC with and without LT. Methods: We performed a retrospective review of patients with PSC and UC evaluated at our institution between 1993 and 2011 who were diagnosed with IND or LGD before or after LT for PSC. The primary end point was neoplasia progression or persistent LGD. Results: Ninety‐six patients (non‐LT n = 63, LT n = 33) were examined. For the IND group, multifocal lesions were significantly associated with time to neoplasia progression [hazard ratio (HR), 3.5; 95% confidence interval (CI), 1.3–9.7], while 5‐aminosalicylate (5‐ASA) use was protective (HR, 0.2; 95% CI, 0.1–0.6). For patients with LGD, multifocal lesions were significantly associated with the primary end point (HR, 7.1; 95% CI, 1.7–28.3), while LT was protective (HR, 0.3; 95% CI, 0.1–0.9). Conclusions: In PSC‐UC patients with IND, 5‐ASA use was associated with a decreased the risk of neoplasia progression, regardless of transplant status. In contrast, multifocal IND and LGD were associated with neoplasia progression or persistent LGD. Patients who developed LGD following LT for PSC were less likely to have progressive neoplasia or persistent LGD, compared with those who had not been transplanted.